Marketing Communication Through Instagram Account @cikadongdong_rivertubing as an Effort to Introduce The Cikadongdong River Tubing Tourism Object in Payung Village, Rajagaluh District, Majalengka Regency - Arun, Regina; Nurfalah, Farida; Wihayati, Welly (Lembaga Penelitian Universitas Swadaya Gunung Jati, 2021)
The research is motivated by the development of technology that support social media as a new dimension in developing the need to find information and knowledge. Social media that is popular among the people one of which is social media instagram, there are also popular accounts in it, one of which is the instagram account @cikadongdong_rivertubing which discusses information about the Cikadongdong River Tubing tourist attraction located in Payung Village, Rajagaluh Sub-district, Majalengka Regency presented in the form of photos and videos and there is information to explain the photos and videos uploaded. The aim of this research is (1) To find out how marketing communication through instagram as an effort to introduce Cikadongdong River Tubing attractions in Payung Village, Rajagaluh District, Majalengka Regency (2) To find out the marketing communication constraints faced by managers in introducing attractions through instagram (3) To find out the effort made by managers in dealing with obstacles when introducing attractions through instagram. The method of thus research used in this thesis is a descriptive qualitative research method with data collection that carried out by means of interviews, ibservation, and documentation using five informants, one kay informant is the manager and admin of the instagram account @cikadongdong_rivertubing, and four supporting informants namely visitor and followers of the instagram account @cikadongdong_rivertubing. The results of the study concluded that, (1) Marketing communication through social media instagram in the digital age is an effective way of being able to attract visitors (2) The obstacle faced by the instagram account admin @cikadongdong_rivertubing is the lack of public interest in reading (3) The effort made by the instagram account admin @cikadongdong_rivetubing in dealing with obstacles is to clarify the caption with an interesting photo upload.